PENGEMBANGAN PRODUKSI BIOGAS DARI LIMBAH PEMBUATAN BIODIESEL JARAK PAGAR (Jatropha curcas seed cake) - Y Yufidani; Bakti Jos; Siswo Sumardiono (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro, 2013)
Biogas is a fermentation process using anaerobic bacteria to convert organic compounds into gas with high composition of methane. Use of jatropha curcas as a biodiesel’s resources remains a problems, seed cake of jatropha curcas contains phorbol esters that is toxic. This research focused on getting an optimum yield of biogas production from jatropha curcas seed cake using additive material to reach optimum C/N ratio. Optimum C/N ratio on biogas production was range 20-30, but jatropha curcas seed cake had C/N ratio about 9/1, so it needs to be added carbon source in order to achieve optimum C/N ratio. Carbon sources that added were paddy straw and tapioca wastewater as a solvent. Process of biogas production in this research use 3 variables, that are the number of jatropha seed cake total solid, the addition of paddy straw, and using tapioca wastewater as solvent. The result showed that the optimum composition in biodigester was jatropha seed cake 6% w/v, paddy straw 3% w/v, ruminant bacteria 10% v/v, and water as solvent. The yield of biogas reached 0,163 m3/kg total solid.